Educational inequality in Latin America: The case of early childhood (Educational Knowledge, 2025)
This study aimed to identify some of the repercussions of social inequalities related to the quality and access to education for children aged zero to six. Literature on educational quality and the structural and social problems embedded in education was reviewed. Measures taken by governmental and international institutions in response to the arrival of SARS-CoV-2 were explored, along with perspectives from authors who advocate for educational innovations as a potential solution.The discussion considered aspects such as teaching practices, schooling beyond access, and the situation of early childhood populations within the education sector—where the younger the child, the greater the inequality. By the 2000s, access to education had significantly expanded, although this did not necessarily reflect improved quality. The study also encourages reflection on educational reforms achieved through social efforts. Ultimately, it was found that the pandemic posed a critical challenge to the education system, being one of the sectors most affected in the medium term.
Keywords: Social inequality; Latin America; teaching practices; early childhood